Has the damage been done? : examining the effects of legal synthetic cannabis and subsequent effects of prohibition on synthetic cannabis and other illicit drug use : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University, New Zealand - Robertson, Kristy (Massey University, 2015)
Synthetic cannabinoids are chemically produced psychoactive substances, which are the most recent trend in designer drugs in New Zealand, and until the 8th of May 2014, were purchased freely in retail stores throughout New Zealand. Synthetic cannabis was marketed as a “safe” alternative to natural cannabis; however, its harm profile has been considered greater than other illicit substances. The objectives of the current study were to examine the prevalence of synthetic cannabis use and how previous users have responded to prohibition, and to assess the physiological and psychological harms associated with consumption. Participants (N = 94) self-selected to participate in the study and were recruited from the community. They completed a computerised structured questionnaire that was designed for the study and incorporated two measures, the Severity of Dependence Scale and Brief Symptom Inventory. Results indicated that there was a significant decrease in the frequency of synthetic cannabis use following prohibition, although 40% of participants reported that they would continue to source synthetic cannabis illegally. While most participants reported fairly minor issues from use, some respondents noted more serious physiological and psychological problems, including coma, chest pain, breathlessness, seizures, and psychosis. Nearly one-quarter of participants (25%) reported that they required emergency care following synthetic cannabis use. High rates of dependency (72%) were detected in the sample and participants’ average psychological symptom profile was of a magnitude to be considered in the clinical range for psychological distress, although there were no significant differences in psychological well-being between current synthetic cannabis users and current non-drug users. Following synthetic cannabis prohibition, there was a significant decrease in illicit substance use across all drug categories and only a small number of participants (3%) had started using legal synthetic cannabis and progressed to using other illicit drugs. Of concern is that 32% of participants reported using methamphetamine and not using this substance in the past, with 14% of the sample going on to use methamphetamine regularly as an alternative to synthetic cannabis. Findings are interpreted in relation to previous research and limitations of the study are highlighted. Recommendations are made for future research, including examining the long-term effects and chronic exposure to the adverse toxicities of synthetic cannabis.
Keywords: Designer drugs; Synthetic cannabis; New Zealand